Absolute pore size distributions from NMR - Sørland, Geir Humborstad; Djurhuus, Ketil; Widerøe, Hege C.; Lien, Jan R.; Skauge, Arne (Diffusion Fundamentals, 2007)
NMR measurements on core samples saturated with brine returns valuable information on the porous structure of the rock core. Monitoring a single fluid component in a relaxation experiment reflects the pore size distribution and thus the degree of sorting of the porous rock. The basic assumptions are that the mobility of the component confined in the porous rock is of such a value that a small fraction of the probing molecules experience the surfaces of the pores and that the surface relaxation strength is fairly independent of pore size. Then one may combine diffusion measurements at short observation times returning a value for the average surface to volume ratio with ordinary relaxation time measurements to obtain an absolute pore size distribution instead of the standard T2 distributions or T1-T2 correlated two dimensional distributions.